2014
DOI: 10.1111/pai.12281
|View full text |Cite|
|
Sign up to set email alerts
|

Neonatal hyperbilirubinemia and childhood allergic diseases: a systematic review

Abstract: CRD42014009943]. Of 79 citations retrieved, a total of 7 good quality studies (n = 101,499) were included in the final analysis. There was a significant increase in the odds of asthma and allergic rhinitis (AR) after NNH [asthma, OR 4.26 (95% CI 4.04-4.5); AR, OR 5.37 (95% CI 4.16-6.92)] and after NPT [asthma, OR 3.81 (95% CI 3.53-4.11); AR, OR 3.04(95% CI 2.13-4.32)]. A similar increase in the trend was noted for late onset of asthma after NNH [OR 4.1 (95% CI 2.82-5.94)], and hospitalization due to asthma aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 24 publications
1
20
1
7
Order By: Relevance
“…A meta-analysis of seven studies (six retrospective studies and one cohort study) including 101,499 children 18 showed that neonatal hyperbilirubinemia significantly increased the odds of childhood asthma (OR=4.26), without heterogeneity across studies. Neonatal phototherapy also increased the odds of asthma (OR=3.81) with low heterogeneity.…”
Section: Perinatal Factors (Figure 2b)mentioning
confidence: 99%
“…A meta-analysis of seven studies (six retrospective studies and one cohort study) including 101,499 children 18 showed that neonatal hyperbilirubinemia significantly increased the odds of childhood asthma (OR=4.26), without heterogeneity across studies. Neonatal phototherapy also increased the odds of asthma (OR=3.81) with low heterogeneity.…”
Section: Perinatal Factors (Figure 2b)mentioning
confidence: 99%
“…Accordingly, neonatal jaundice was associated with the development of allergic diseases, mostly allergic rhinitis and AD, in a population‐based study . Furthermore, this risk was linked with high bilirubin levels requiring phototherapy . The pathophysiology of the relationship between neonatal jaundice and allergic consequences remains unclear and warrants further exploration.…”
Section: Perinatal Influencesmentioning
confidence: 99%
“…Additionally, previous studies could not find an association between phototherapy and skin cancer [16,19]. Phototherapy does seem to be associated with the development of allergic diseases [20].…”
Section: Intensive Phototherapymentioning
confidence: 99%